The Role of Leadership on Performance Through Work Motivation of South Sulawesi Regional Police Personnel - Yusnita, Yusnita; Daga, Rosnaini; Hatta, Moh (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study examines the influence of leadership on personnel performance through work motivation at the South Sulawesi Regional Police (POLDA Sulsel). The research adopts a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze the relationships among leadership, motivation, and performance. The sample consists of 81 police personnel, selected using Accidental Sampling. Data were collected through structured questionnaires and analyzed with SmartPLS 4 software. The results indicate that leadership has a significant and positive effect on work motivation (β = 0.958, p < 0.05) and personnel performance (β = 0.911, p < 0.05). However, work motivation does not significantly affect personnel performance (β = 0.223, p > 0.05), and its mediating role between leadership and performance is insignificant (β = 0.155, p > 0.05). These findings suggest that leadership is a key determinant of personnel performance, whereas motivation alone is not a primary driver of performance in a structured law enforcement environment. The study recommends that POLDA Sulsel enhance leadership development programs to optimize personnel performance. Future research could explore additional factors such as organizational culture, job satisfaction, and institutional policies to further understand the determinants of performance within law enforcement agencies